Asuhan Keperawatan Jiwa pada Klien dengan Resiko Perilaku Kekerasan di Wisma Melati Rmah Sakit Jiwa Prof Dr HB Saanin Padang - Alya Irwana Putr; Ramaita Ramaita; Dwi Happy Anggia Sari; Vivi Yuderna (CV. ITTC INDONESIA, 2026)
The risk of violent behavior is one of the angry responses expressed by making threats, injuring oneself or others and can damage the surrounding environment. Based on data from medical records at Prof. HB. Saanin Mental Hospital, Padang, the nursing problem in the last three years is the risk of violent behavior with a total of 573 clients. The purpose of this case study is to be able to apply psychiatric nursing care to patients with a risk of violent behavior at Prof. HB Saanin Mental Hospital, Padang. The application method used is a case study conducted on the client by approaching using the nursing process, namely assessment, diagnosis, intervention, implementation and evaluation. The results of the assessment showed that the client experienced signs and symptoms of the risk of violent behavior in the form of damaging household furniture, breaking glass, sharp eyes, and being easily offended. The main diagnosis that emerged was the risk of violent behavior with a companion diagnosis of self-care deficit. After nursing care is carried out, the client can do it independently through the Implementation Strategy, namely, SP 1 trains how to control anger by doing physical exercises 1 and 2 (Deep breathing and hitting a pillow), SP 2 by taking medication correctly, SP 3 is speaking verbally (expressing, asking and refusing correctly) and SP 4 is training spiritually/doing 2 selected activities (reciting dhikr and istighfar). It is hoped that through this research, everyone can realize the importance of maintaining mental health.